Forage growing offers multiple possibilities for income generation and job creation - Ohmstedt, Uwe (Bioversity International and the International Center for Tropical Agriculture, 2021)
Different activities directly related to forage growing offer possibilities for income generation. Forage growing and feeding to the cows is significantly changing the dairy farms situation. It is improving the cows diet, the health status, the milk yield and such directly the profitability of the dairy farms. Feeding accounts for up to 70% of diary production costs which can be reduced by producing high value forage on farm. Forage growing for commercial purposes, being sold as fresh matter or as hay creates possibilities for farmers, even if the do not have the means or the willingness to go themselves into dairy production. Service provision as seedling producers or for silage making are other ways to profit from forage growing.